Fiscal decentralization and the challenges of public ecological services delivery - N.V. Kotenko; T.O. Illyashenko (Marketing i Menedžment Innovacij, 2015)
The aim of the article. The aim of the article is to define and propose the directions to solve the recent problems of financing public ecological services in the conditions of fiscal decentralization. The results of the analysis. This paper analyzes the decentralization reform impact on the possibilities of local authorities to finance the public ecological services in Ukraine. Advantages and threats of decentralizing reform are defined on the basis of theoretical vision of fiscal federalism in different state structures. The authors assessed basic central government documents in which the strategy and tactic of development. The lack of particular measures that are directed to the sustainable nature use on state level is defined. In practice, this means transference of financing powers from central to local government. Such process needs to be conducted with respective changes of financial flows directions and establishing effective forming and distributive tools. Traditionally, one of such tools, which are most appropriate to accumulate public environmental funds, is ecological tax. The study revealed that the enhancement of general fund of local budget revenues by local tax make the Local Environmental foundations' work impossible. Another initiative of central government is to transfer more than half revenues from the tax to the regional level. Such decision will be practicable only if impartial, formula based mechanism of subsequent allocation of funds between basic local authorities is developed. Scale projects now are funded by regional authorities. Authors proved that the better way to finance public ecological services on complementary basis is the local authorities’ cooperation. One of the advantages of such cooperation is the considering of the opportunities of self-taxation. This voluntary fiscal tool in Ukrainian European future must be stable source for financing of public ecological services. Decentralization reform also provides for the official consolidation of local authorities which meets lots of resistance from communities. To overcome obstacles and make it really voluntary there are propositions to account natural marks and distributive criteria basing on ecosystem approach. The analysis of financial autonomy of local budgets shows that the prior part of local public revenues continues to form by intergovernmental fiscal transfers. For the purpose to provide sustainable development of communities authors propose to include ecological components into the system of budget equalization and compensation. This paper proves the inadequacy of horizontal equalization procedures for management of the system of general territorial nature use. The main reason for it is the inferior fiscal potential of the state environment tax and payments fixed attached to the local budgets. On the contrary, establishment of the ecological subsidies to the budget management allows to finance the local projects of expanded reproduction of territory and its ecological infrastructure. To resolve this problem authors propose to assess the quantity of ecological subsidy basing on the next parameters: the amount of population of rated community (political unit); the financial standard of budgetary provision of ecological services, compensate coefficients. The compensate coefficients must be individual to particular territory and take into account the ecological degradation pace, the efficiency and experience of ecological public program implementation, the tendency of degradation of independent nature components that is in keeping with existent levels of man's impact, the particularity of ecological service provisioning in exclusion zone. Conclusions and directions of further researches. To summarize, reform of fiscal decentralization in Ukraine is really needed and has opportunities. But it needs prudence and accurate economic ground. Cooperation and consolidation of communities on the basis of common interests and needs of sustainable development lead to improve the Ukrainians’ life quality and to increase the efficiency of public services provision. The applications of vertical fiscal compensation procedure allows to equivalence allocate budget revenues and ecological expenditures. But the methodology of ecological self-taxation, assessment and distribution of subsidies need further researches.